The Main Parameters Effect OF Magnet Mass Analyzer And Electrostatic Quadruple Lens ON Beam Line System Design (Journal of the College of Basic Education, 2022)
In this research we consider a design at beam line system consisting of magnet mass analyzer and electrostatic quadruple lenses where changing the parameter (entrance angle α, exit angle β, the distance between the lenses LD and quadruple lens length Lq) .Also we study the action of the system focusing or defocusing by using the beam liner system.